Automatic water system plant / Muhammad Irfan Mohamad Fadhil - Mohamad Fadhil, Muhammad Irfan (2023)
Home gardening offers a relaxing hobby for city dwellers. Frequently, they have to get involved with activities outside of the city which leaves their home gardens unwatered for some time. A drought may increase the atmospheric temperature, especially in the city region. An unwatered garden and extreme heat can lead to fatal dehydration in the plants of a home garden. Most automatic watering systems work on the time-activated system which fail to cater well for raising the temperature. This project works on developing a conceptual prototype of a mobile application watering system for home gardens in urban dwellings. A mobile application (App) is an application software designed to run on a mobile device for performing a specific task by the user. A specific Sonoff device is installed into the house garden watering system. The Sonoff device is a WiFi switch that can be distantly controlled for activating the mobile application watering system house garden watering system. The WiFi switch is initiated using a smartphone App via internet communications. On a very hot day, he can frequently view and water his home garden while working at the office desk. The project has successfully implemented and tested the conceptual prototype of a mobile App house garden watering system.